National Trends of Bladder Cancer and Trihalomethanes in Drinking Water: A Review and Multicountry Ecological Study - Joseph A. Cotruvo; Heather Amato (SAGE Publishing, 2019)
We examined trends in incidence of bladder cancer in 8 countries in the 45+ years since trihalomethanes (THMs) were detected in chlorinated drinking water. Total trihalomethanes (TTHMs) are the principal regulated disinfection by-products (DBPs) along with halogenated acetic acids (HAAs). Numerous epidemiological studies have examined exposure to TTHMs and associations with bladder cancer. Concentrations of TTHM have declined in most of the 8 countries that were studied as has smoking prevalence. Incidences of bladder cancer have usually stayed relatively flat, especially for females, with some variations. Since THMs are not carcinogens in whole animal tests, they may not be appropriate surrogates for studying potential cancer risks in drinking water. Etiology of bladder cancer is complex; incidence correlates with age. Previously identified risk factors include smoking, type 2 diabetes, sex, ethnicity, arsenic, aromatic amines, and occupations. As a predominant risk factor, smoking trends may dominate incidence rates, but additional time might be required to determine whether a DBP risk exists due to long latency periods. Causal drinking water-related bladder cancer risks remain questionable and likely small compared to other factors, although surrogate-based DBP management is an appropriate strategy for maintaining drinking water quality as long as it does not compromise microbial disinfection.